Acute Pyelonephritis in a Dog: A Case Report - Kar, Payel; Rajesh, J B; Das, Manas; Kar, Debalina (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Plonephritis describes inflammation of the renal pelvis as Well as adjacent renal parenchyma. Although ascending infection of the lower urinary tract (LUT) is the primary cause of most episodes of pyelonephritis, hematogenous spread of infection can also occur but less frequently. The disease can be acute or chronic, and unilateral or bilateral (Parry, 2005). About 75% of infections are caused by a single bacterial pathogen; 20% of UTIs are caused by two coinfecting species; and roughly 5% are caused by three species (Olin andBartges, 2015). In both dogs and cats, the bacteria that most frequently result in UTIs are Escherichia coli, Staphylococcus, and various others like Proteus, Klebsiella, Pasteurella, Pseudomonas, Corynebacterium, and several more infrequently reported genera (Ling et al., 2008).